2014
DOI: 10.2514/1.c032340
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Geometry Model for Design Studies of Tailless Supersonic Aircraft

Abstract: This paper presents an extension of the Kulfan class-shape transformation method for the parameterization of aircraft component geometry. The VT-CST code represents a practical implementation of the class-shape transformation method in an object-oriented C++ code for use within a multidisciplinary design optimization framework for design studies of a tailless supersonic aircraft. Extensions to the class-shape transformation method incorporated into VT-CST include the generation of a blended wing-fuselage, cowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…T he Class-Shape Transformation (CST) parametrization method 1, 2, 3 has become an increasingly popular method for creating analytical representations of the surface coordinates of various components of aerospace vehicles. 4,5,6,7 CST parametrization can be used to represent a wide variety of two-and threedimensional shapes with a modest number of parameters, and it provides built-in design variables for use in shape optimization. The use of analytical functions means that the surface representation is smooth and continuous to as fine a degree as desired, without the need for interpolation between discrete points.…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…T he Class-Shape Transformation (CST) parametrization method 1, 2, 3 has become an increasingly popular method for creating analytical representations of the surface coordinates of various components of aerospace vehicles. 4,5,6,7 CST parametrization can be used to represent a wide variety of two-and threedimensional shapes with a modest number of parameters, and it provides built-in design variables for use in shape optimization. The use of analytical functions means that the surface representation is smooth and continuous to as fine a degree as desired, without the need for interpolation between discrete points.…”
Section: Nomenclaturementioning
confidence: 99%
“…In several studies, the planform shape has been specified using simple linear parametrizations for a known class of wing (e.g. a simple subsonic transport wing 9 or a cranked delta wing 6 ). The planform shape has also been specified by defining the chord and leading-edge x and z coordinates using additional analytical functions of η = 2y/b.…”
Section: Nomenclaturementioning
confidence: 99%
“…Morris et al (2014), Nejat et al (2014), and Su et al (2015) have showed the shape of curves for different values of N 1 and N 2 . They also claimed that when describing an airfoil, the values we normally use are N 1 =0.5 and N 2 =1.…”
Section: Parameterization Methodsmentioning
confidence: 99%
“…There are many studies on parametric modeling of HGVs [1], [6], [10], [11] and common methods include the B-spline method [12], [13], non-uniform rational B-spline (NURBS) method [14], class/shape function transformation (CST) method [15], parametric section (PARSEC) method [16], Hicks-Henne method [17], radial basis function (RBF) method [18], and free form deformation (FFD) method [19]. Among these, the FFD method can be used in arbitrary geometrical models and creates arbitrary theoretical deformation results, thereby providing a wide design space.…”
Section: Introductionmentioning
confidence: 99%